Barriers to Counseling: LGBTQ+ Students’ Struggles in Accessing School Counseling Services in a Public School in Northwestern Philippines - Trachaey Mae Dulatre; Maria Elena V. Milan (International Journal of Counseling and Psychotherapy, 2026)
Background: Despite legislative mandates for safe educational environments, LGBTQ+ youth in rural Southeast Asia face persistent minority stress and institutional barriers that deter formal help-seeking, representing an urgent population and practical knowledge gap in current school counseling literature. Objective: This study aimed to critically explore the lived experiences of LGBTQ+ students in accessing school counseling services within a rural Philippine public secondary school. Methods: Employing a qualitative narrative inquiry design, semi-structured interviews were conducted remotely via Google Meet with ten purposively sampled LGBTQ+ senior high school students (Grades 11–12, aged 16–17) and analyzed using Braun and Clarke’s thematic analysis framework. Results: Findings revealed that fears of confidentiality breaches, anticipated teacher bias, misgendering, and rigid uniform and haircut mandates severely diminished institutional trust, compelling marginalized learners to rely on peer alliances and digital subcultures as alternative coping mechanisms. Conclusion: Physical counseling offices do not guarantee emotional safety; guidance spaces remain precarious environments requiring a paradigm shift toward proactive, advocacy-based counseling models. Originality/Value: This study contributes to Guidance and Counseling and School Psychology by providing an empirically grounded framework on minority stress dynamics within an underrepresented provincial Southeast Asian context. The findings enrich existing empirical evidence and serve as a strategic benchmark for educational policymakers and school administrators to mandate practitioner cultural competence training, revise binary disciplinary codes, and institutionalize gender-affirming curriculum.